PENGARUH NON PERFORMING LOAN, BIAYA OPERASIONAL PENDAPATAN OPERASIONAL DAN LOAN TO DEPOSIT RATIO TERHADAP RETURN ON ASSET PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2015 - 2019 - DUMARIANI SILALAHI; BERTHA NERPY SIAHAAN (LP2MTBM MAKARIOZ, 2021)
The research methodology used is multiple linear regression analysis. The results of the study prove that the Non PerformingLoan and the Loan to Deposit Ratio have no and insignificant effect on the Return on Assets of Banking Companies Listedon the Indonesia Stock Exchange for the 2015-2019 Period. Operating Costs Operating Income has a significant andsignificant effect on Return on Assets in Banking Companies Listed on the Indonesia Stock Exchange for the 2015-2019Period. Non Performing Loans, Operating Costs, Operating Income and Loan to Deposit Ratio have an effect and aresignificant on Return on Assets in Banking Companies Listed on the Indonesia Stock Exchange for the 2015-2019 Period.The adjusted coefficient of determination (R Square) obtained a value of 0.484, meaning that the independent variables,namely Non Performing Loans, Operating Costs and Operating Income, and Loan to Deposit Ratio have an effect on theReturn on Assets variable by 48.4% and 51.6% are influenced by other variables not used in this study such as net profitmargin, company size, third party funds and capital.